ChemInform Abstract: Preparation, Structure and Luminescence Properties of Ba2V2O7 Microrods. Issue 49 (17th November 2016) - Yu, Ruijin; Yuan, Maosen; Li, Tianbao; Tu, Qin; Wang, Jinyi
Abstract: Self‐activated Ba2 V2 O7 phosphor microrods are prepared by hydrothermal reaction of Ba(NO3 )2 and V2 O5 in aq.